Laparoscopic Versus Open Surgical Repair of Anorectal Malformations: A Systematic Review and Meta-Analysis - Amani N. Alansari (19743643) (2025)
Background Laparoscopic-assisted anorectoplasty (LAARP) and posterior sagittal anorectoplasty (PSARP) are established procedures for the treatment of high and intermediate anorectal malformations (ARMs). Their comparative outcomes remain under investigation. Objective To compare the outcomes of LAARP and PSARP in children with high and intermediate ARMs. Methods PubMed, Web of Science, Scopus, and the Cochrane Library were searched from database inception up to April 2025 for prospective studies comparing LAARP and PSARP. Data were analyzed using Review Manager (RevMan) 5.4. A fixed-effect model was primarily used for data synthesis. However, a random-effects model was applied in cases of significant heterogeneity. Results Eight studies were included, of which 6 contributed data to the quantitative synthesis. LAARP demonstrated significantly better functional continence scores than PSARP at 1-year follow-up (SMD = 0.58; 95% CI: 0.08-1.08; P = .02; I2 = 34%). Operative time was longer in the LAARP group, though not statistically significant (MD = 133.16 minutes; 95% CI: −26.45 to 292.77; P = .10; I2 = 96%). The length of hospital stay was significantly shorter in the LAARP group (MD = −3.45 days; 95% CI: −4.47 to −2.61; P < .00001; I2 = 54%). LAARP was associated with potentially higher rates of anal stenosis (RR = 1.48; 95% CI: 0.62-3.55; P = .38; I2 = 4%) and rectal prolapse (RR = 2.15; 95% CI: 0.84-5.48; P= .11; I2 = 9%), though differences did not reach statistical significance. Conclusion LAARP offers improved short-term continence and shorter hospital stay compared with PSARP in children with high and intermediate ARMs. Further large multicenter randomized trials with long-term follow-up are needed to confirm these findings. Other Information Published in: Sage Open Pediatrics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/30502225251401658